If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 = 10 + z Solving 40 = 10 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. 40 + -1z = 10 + z + -1z Combine like terms: z + -1z = 0 40 + -1z = 10 + 0 40 + -1z = 10 Add '-40' to each side of the equation. 40 + -40 + -1z = 10 + -40 Combine like terms: 40 + -40 = 0 0 + -1z = 10 + -40 -1z = 10 + -40 Combine like terms: 10 + -40 = -30 -1z = -30 Divide each side by '-1'. z = 30 Simplifying z = 30
| 14x+1+5x-7=89 | | 8a-19=3a+5 | | z+5-4*z=8 | | 70-t=50 | | 9x+10=17+2x | | 81m^2=49 | | 7+3(2x+5)+4=2x-2(3x+8) | | 2(-x+1)-6x=30 | | c-2*c-5-5*c=7 | | 8e^2+64e=-56 | | -2t+4t+-7s=9s | | 3+x=7x-21 | | p+15=15 | | 5(-3x+5)=25 | | 16=10c-c^2 | | 3*w+4*w-2=12 | | 5m+8=78 | | 98-r=28 | | 7(4n-7)(7n-4)=0 | | 0.5*x*(x+4)=20 | | x(2x-5)(5x+2)=0 | | x^2-10+25=4 | | 3+x=7x+-21 | | x^2*8=32 | | 16m+8=32 | | 7(-4-4x)=308 | | 6(6-15)+16+6= | | y^2+12y-45=0 | | (-7)(-5)+(-7)(-4)= | | ln(x)+ln(x+2)=8 | | 11=5*y-4 | | xy=15x^2 |